Shb deficiency in endothelium but not in leucocytes is responsible for impaired vascular performance during hindlimb ischaemia. (17th January 2015) - Nikpour, M.; Gustafsson, K.; Vågesjö, E.; Seignez, C.; Giraud, A.; Phillipson, M.; Welsh, M.
Abstract Aim Myeloid cells have been suggested to participate in angiogenesis and regulation of vascular function. Shb‐deficient mice display both vascular and myeloid cell abnormalities with possible consequences for recovery after hindlimb ischaemia. This study was conducted in order to assess the contribution of Shb deficiency in myeloid cells to impaired vascular function in ischaemia. Methods Wild type and Shb‐deficient mice were subjected to peritoneal vascular endothelial growth factor A (VEGFA) followed by intraperitoneal lavage, after which blood and peritoneal cells were stained for myeloid markers. VEGFA‐induced leucocyte recruitment to cremaster muscle was investigated using intravital microscopy of both mouse strains. Blood flow after femoral artery ligation was determined on chimeric mice after bone marrow transplantation. Results No differences in neutrophil numbers or cell surface phenotypes were detected. Moreover, neutrophil extravasation in VEGFA‐activated cremaster muscle was unaffected by Shb deficiency. However, blood and peritoneal CXCR4+ monocytes/macrophages were reduced in response to intraperitoneal VEGFA but not lipopolysaccharide (LPS) in the absence of Shb. Furthermore, the macrophage population in ischaemic muscle was unaffected by Shb deficiency after 2 days but reduced 7 days after injury. The bone marrow transplantation experiments revealed that mice with wild type vasculature showed better blood flow than those with Shb‐deficient vasculature irrespective of leucocyte genotype. Conclusion The observed aberrations in myeloid cell properties in Shb‐deficient mice are likely consequences of an abnormal vascular compartment and are not responsible for reduced muscle blood flow. Structural vascular abnormalities seem to be the primary cause of poor vascular performance under provoked vascular stress in this genetic model.